Respuesta :
The best and most correct answer among the choices provided by your question is the second choice or letter B. The formula can be f(x) = 3(4)x − 1
If f(2)=12 then f(2+1)=4(12) Now go to the general formula for a geometric sequence.an=a1∗r(n−1)
Since f(3)=48 and f(2)=12 or you can say
a3=48anda2=12
Sincer=an+1an
then r= 48/12 or 4 Now finda1
from the formula for n=348=a1∗4(3−1)
Soa1=3
So it looks likef(x)=3∗4x−1
If f(2)=12 then f(2+1)=4(12) Now go to the general formula for a geometric sequence.an=a1∗r(n−1)
Since f(3)=48 and f(2)=12 or you can say
a3=48anda2=12
Sincer=an+1an
then r= 48/12 or 4 Now finda1
from the formula for n=348=a1∗4(3−1)
Soa1=3
So it looks likef(x)=3∗4x−1
Answer : B.) f(x) =[tex]f(x) = 3(4)^{n-1} [/tex]
The recursive formula f(x+1) = 4f(x)
Given : second term is 12 , so f(2) = 12
f(3) = 4f(2) = 4 * 12 = 48
f(4) = 4f(3) = 4*48 = 192
f(2) = 12 = 4* 3= 4*f(1). So f(1) = 3
f(1) =3 , f(2) = 12, f(3) = 48, f(4)=192.....
The sequence is Geometric
We use geometric sequence formula
[tex]f(x) = ar^{n-1} [/tex], where 'a' is the first term and 'r' is the common ratio
a= 3 and r= 4
Explicit formula is [tex]f(x) = 3(4)^{n-1} [/tex]